CAVITATION PREVENTATION IN CENTRIFUGAL PUMPS USING ANSYS - Doria, Aldair; Rodríguez Toscano, Andrés; Ramírez Restrepo, Rafael (Journal of Applied Engineering Science, 2023)
In this paper, a computational fluid dynamic (CFD) model was developed to assess cavitation phenomenon and its local effects on a centrifugal pump. The model included the temperature of the fluid, rotational velocity, and geometric configuration of the suction. The model was validated using the pump characteristics curves of the manufacturer with an error of 5%. Also, the minimum pressure contours and the vapor volume fraction were plotted. These contours show the pump boundary conditions (temperature and angular velocity) before cavitation occurs. Thus, the impeller zone where the cavitation phenomenon is more susceptible to occurrence was identified. In addition, this analysis determined characteristic parameters such as the limit on fluid temperature, the limiting angular velocity of the pump and the ratio between the diameters of the suction pipe and the pump inlet diameter. The proposed methodology is aimed as a reference for the study of local operating parameters to avoid cavitation in various types of hydraulic pumps.